The structure of the Tamil verb - Sathasivam, A (1956)
The study of the verbal forms occurring in the Cankam texts (date about 50 B.C. - 250 A.D.) reveals that at least two of them namely kalittokai and paripātal possess forms of later origin. In the language of the other sixteen texts, many distinct features of the Old Tamil have been observed. The development of the Tamil language began to take a new turn from the period of kalittokai. Therefore the Old Tamil features as seen in the verbal forms of the earlier texts are of much importance especially to understand the true nature of the Dravidian verb. Continued in thesis ...